The Role of Adopting International Public Sector Accounting Standards (IPSASs) in Achieving Financial Sustainability for Universities - Muhsein Hameed*, Anmar; Najem Aubdullah Al-Mashhadani , Bushra (Journal of Economics and Administrative Sciences, 2024)
The research objective is to determine whether using the International Public Sector Accounting Standards (IPSASs) has any impact on assessing the financial sustainability of public universities. The research assesses the role played by financial sustainability in maintaining, expanding and how well the services are executed through public universities. Additionally, considering the occasional and future challenges of the information that supplied by the accounting system. The government accounting system applied in Iraqi public universities suffers from the lack of information for those in charge of setting financial policies up in those universities when assessing financial sustainability. To achieve the objective of the research, a questionnaire was designed and distributed to a sample of holders of postgraduate degrees who have sufficient academic qualifications and experience, the sample included 126 academics and professionals. The analysed results reveal that financial sustainability has a great role in elevating the quality and sustainability of the university learning outcomes in public universities. Also, the current government accounting system that is based on the monetary basis suffers from several deficiencies in assessing financial sustainability. The results also show that IPSAS implementation based on the accrual method would contribute to the evaluation of the public university financial sustainability by providing information, which reflects the financial situation and the outcome of the activity in a fair manner by means of improving both the relevance and credibility of representing accounting information and the objectivity of financial statement informational content.